2012
DOI: 10.1074/mcp.m112.017608
|View full text |Cite
|
Sign up to set email alerts
|

The Balance in the Delivery of ER Components and the Vacuolar Proton Pump to the Phagosome Depends on Myosin IK in Dictyostelium

Abstract: In Dictyostelium, the cytoskeletal proteins Actin binding protein 1 (Abp1) and the class I myosin MyoK directly interact and couple actin dynamics to membrane deformation during phagocytosis. Together with the kinase PakB, they build a regulatory switch that controls the efficiency of uptake of large particles. As a basis for further functional dissection, exhaustive phagosome proteomics was performed and established that about 1300 proteins participate in phagosome biogenesis. Then, quantitative and comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…To establish the mechanism underlying the defects in degradation, we used quantitative comparative proteomics to identify differentially represented proteins in the isolated phagosomes of Ax2, WASH , and FAM21 mutants (Dieckmann et al ., 2012; Gotthardt et al ., 2006a). To confirm this approach, we first looked at the levels of v-ATPase.…”
Section: Resultsmentioning
confidence: 99%
“…To establish the mechanism underlying the defects in degradation, we used quantitative comparative proteomics to identify differentially represented proteins in the isolated phagosomes of Ax2, WASH , and FAM21 mutants (Dieckmann et al ., 2012; Gotthardt et al ., 2006a). To confirm this approach, we first looked at the levels of v-ATPase.…”
Section: Resultsmentioning
confidence: 99%
“…They have also been functionally clustered with the help of the DAVID functional annotation clustering tool ( Figure 4C and Table S2). Comparison of the MCV proteome functional classification with the previously published phagosome proteome classification (Dieckmann, Gueho et al 2012) indicated that overall, these compartments are very similar (Figure 4B). This again confirms that the MCV conserves some of its phagosomal identity.…”
Section: Marinum MCV Proteomementioning
confidence: 61%
“…In order to study the MCV proteome, the first step of this study has been to establish an experimental strategy to isolate pure fractions of those compartments from infected D. discoideum cells. We decided to adapt the efficient method to isolate pure fractions of latex beads-containing phagosomes (LPCBs) described previously (Dieckmann, Gueho et al 2012). This method is based on the light buoyant density and flotation properties of latex beads.…”
Section: Establishment Of a New Procedures To Isolate Mycobacteria-conmentioning
confidence: 99%
“…The regulation of ER dynamics in D. discoideum has not been under extensive investigation. Involvement of the class I myosin MyoK in the delivery of ER membranes to the early phagosome has been reported, and recruitment of calnexin-positive ER to Legionella pneumophila-containing vacuoles (45,46). From the published data, it is reasonable to assume that the ER associates with the actin and the microtubule cytoskeletons in D. discoideum.…”
Section: Discussionmentioning
confidence: 87%